Liquid crystal polyester composition, method for producing liquid crystal polyester composition, and molded article
By introducing specific olefin-based copolymers into the liquid crystal polyester composition, the structure of the liquid crystal polyester is optimized, and the improvement space for the existing liquid crystal polyester composition in terms of heat resistance and tensile elongation is solved, thereby achieving higher heat resistance and tensile elongation.
Patent Information
- Application Number
- CN202380060674.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-13
- Filing Date
- 2023-09-13
- Publication Date
- 2025-04-04
AI Technical Summary
The existing liquid crystal polyester compositions have room for improvement in heat resistance and tensile elongation.
The structure of the liquid crystal polyester is optimized by introducing a specific olefin-based copolymer into the liquid crystal polyester composition, including repeating unit A derived from olefin monomers of 2 to 8 carbon atoms and repeating unit B with glycidyl groups.
The heat resistance and tensile elongation of the liquid crystal polyester composition are significantly improved, while the dielectric loss tangent and melt viscosity are controlled, and the performance of the molded body is improved.
Smart Images

Figure BDA0005277013370000171 
Figure BDA0005277013370000172 
Figure BDA0005277013370000341
Abstract
Description
Technical Field
[0001] The present disclosure relates to a liquid crystal polyester composition, a method for producing the liquid crystal polyester composition, and a molded body.
[0002] This application claims priority based on Special Application No. 2022-149236 filed in Japan on September 20, 2022 and Special Application No. 2023-003766 filed in Japan on January 13, 2023, and the contents of which are incorporated herein by reference. Background Art
[0003] Liquid crystal polyester is generally called a melt liquid crystal type (thermotropic liquid crystal) polymer, which has extremely excellent melt fluidity and has a heat resistance of more than 300°C due to its structure. Liquid crystal polyester is used for automotive parts represented by electronic parts, OA parts, and heat-resistant tableware due to its high fluidity and high heat resistance.
[0004] In recent years, in order to reduce dielectric loss in application to next-generation communication technology, materials showing a low dielectric constant and a low dielectric loss tangent have been required.
[0005] As a material showing a low dielectric constant and a low dielectric loss tangent, Patent Document 1 discloses a resin composition comprising a liquid crystal polyester resin containing a structural unit derived from a hydroxycarboxylic acid, a structural unit derived from a diol compound, and a structural unit derived from a dicarboxylic acid, and a fluororesin.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: International Publication No. 2020 / 138277 Summary of the invention
[0009] Problems to be solved by the invention
[0010] However, there is still room for research on improving the heat resistance and tensile elongation of liquid crystal polyester compositions.
[0011] The present disclosure has been made to solve the above-mentioned problems, and an object of the present invention is to provide a liquid crystal polyester composition having excellent heat resistance and tensile elongation.
[0012] Another object of the present disclosure is to provide a method for producing a liquid crystal polyester composition having excellent heat resistance and tensile elongation.
[0013] Furthermore, an object of the present disclosure is to provide a molded body including the above-mentioned liquid crystal polyester composition.
[0014] Means for solving problems
[0015] The inventors have conducted intensive studies to solve the above problems and, as a result, have found that heat resistance and tensile elongation are improved by containing a specific olefin-based copolymer in a liquid crystal polyester composition, thereby completing the present disclosure.
[0016] That is, the present disclosure has the following aspects.
[0017] <1> A liquid crystal polyester composition comprising:
[0018] Liquid crystal polyester, and
[0019] Olefin copolymers,
[0020] The olefin-based copolymer includes a repeating unit A derived from an olefin monomer having 2 to 8 carbon atoms and a repeating unit B having a glycidyl group.
[0021] <2> According to the above <1> The liquid crystal polyester composition, wherein the liquid crystal polyester has a repeating unit containing a naphthalene structure, and the content of the repeating unit containing a naphthalene structure is greater than 40% relative to 100% of the total number of all repeating units in the liquid crystal polyester.
[0022] <3> According to the above <1> or <2> The liquid crystal polyester composition, wherein the liquid crystal polyester has repeating units derived from hydroxycarboxylic acid, and the content of the repeating units derived from hydroxycarboxylic acid is more than 50% relative to 100% of the total number of all repeating units in the liquid crystal polyester.
[0023] <4> According to the above <1> ~ <3> In any one of the liquid crystal polyester compositions, the content of the repeating unit B is less than 6% by mass based on 100% by mass of the total mass of the olefin-based copolymer.
[0024] <5> According to the above <1> ~ <4> In any one of the liquid crystal polyester compositions, the content of the repeating unit A is more than 94% by mass based on 100% by mass of the total mass of the olefin-based copolymer.
[0025] <6> According to the above <1> ~ <5> The liquid crystal polyester composition according to any one of the preceding claims, wherein the flow start temperature is higher than 271°C.
[0026] <7> According to the above <1> ~ <6> The liquid crystal polyester composition according to any one of the preceding claims, wherein the content of the liquid crystal polyester is 80% by mass or more relative to 100% by mass of the total mass of the liquid crystal polyester composition.
[0027] <8> Above <1> ~ <7> The method for producing a liquid crystal polyester composition according to any one of the preceding claims comprises mixing a liquid crystal polyester with an olefin-based copolymer,
[0028] The olefin-based copolymer includes a repeating unit A derived from an olefin monomer having 2 to 8 carbon atoms and a repeating unit B having a glycidyl group.
[0029] <9> A molded body comprising the above <1> ~ <7> The molded article of the liquid crystal polyester composition described in any one of the preceding claims, wherein
[0030] The molded article is a connector, a socket, a relay component, a coil frame, an optical pickup, an oscillator, a semiconductor package, an IC tray, a wafer carrier, a household electrical appliance component, a lighting fixture component, an audio product component, a ferrule for an optical cable, a telephone component, a fax component, a modem component, a separation claw, a heater bracket, an impeller, a fan gear, a gear, a bearing, a motor component, a motor housing, an engine component, an engine room component, an electrical component, an automobile interior decoration component, a microwave cooking pot, a heat-resistant tableware, a floor material, a wall material, a beam, a column, a roof material, an aircraft component, a spacecraft component, a space equipment component, a nuclear reactor, a marine facility component, a washing fixture, an optical equipment component, a valve, a pipe, a nozzle, a filter, a membrane, a medical equipment component, a medical material, a sensor component, a sanitary spare part, a sports product or a leisure product.
[0031] Effects of the Invention
[0032] According to the present disclosure, a liquid crystal polyester composition having excellent heat resistance and tensile elongation can be provided.
[0033] Furthermore, according to the present disclosure, a method for producing a liquid crystal polyester composition having excellent heat resistance and tensile elongation can be provided.
[0034] Furthermore, according to the present disclosure, a molded product including the above-mentioned liquid crystal polyester composition can be provided. DETAILED DESCRIPTION
[0035] Hereinafter, embodiments of the liquid crystal polyester composition, the method for producing the liquid crystal polyester composition, and the molded product disclosed herein will be described.
[0036] 《Liquid crystal polyester composition》
[0037] The liquid crystal polyester composition of the embodiment contains a liquid crystal polyester and an olefin-based copolymer, wherein the olefin-based copolymer includes a repeating unit A derived from an olefin monomer having 2 to 8 carbon atoms (hereinafter also referred to as repeating unit A) and a repeating unit B having a glycidyl group (hereinafter also referred to as repeating unit B).
[0038] Since the liquid crystal polyester composition of the embodiment contains the olefin-based copolymer, it is superior in heat resistance compared to a composition not containing the olefin-based copolymer, and the value of tensile elongation when formed into a molded article is improved.
[0039] Hereinafter, the liquid crystal polyester and the olefin-based copolymer contained in the liquid crystal polyester composition of the embodiment, and optional components that may be contained as needed will be described.
[0040] In addition, the liquid crystal polyester composition of the embodiment may contain these in the form of a reaction product of a liquid crystal polyester and an olefin-based copolymer.
[0041] <Liquid Crystal Polyester>
[0042] The liquid crystal polyester contained in the liquid crystal polyester composition of the present embodiment is not particularly limited as long as it is a polyester resin showing liquid crystal properties in a molten state. It should be noted that the liquid crystal polyester may also be a liquid crystal polyester amide, a liquid crystal polyester ether, a liquid crystal polyester carbonate, or a liquid crystal polyester imide.
[0043] The flow start temperature of the liquid crystal polyester may be 250° C. or higher, 270° C. or higher, or 280° C. or higher.
[0044] The flow start temperature of the liquid crystal polyester may be 400° C. or lower, 360° C. or lower, or 340° C. or lower.
[0045] For example, the flow start temperature of the liquid crystal polyester may be 250° C. to 400° C., 270° C. to 360° C., or 280° C. to 340° C.
[0046] In this specification, the flow start temperature is also called fluid temperature or flow temperature, which is a temperature that serves as a standard for the molecular weight of liquid crystal polyester (see Naoyuki Koide, "Liquid Crystal Polymers - Synthesis, Forming, and Applications -", CMC Co., Ltd., June 5, 1987, p. 95).
[0047] In this specification, the flow start temperature of the liquid crystal polyester is measured by using a flow tester to test the liquid crystal polyester at 9.8 MPa (100 kg / cm 2 ) at a temperature at which the liquid crystal polyester exhibits a viscosity of 4800 Pa·s (48000 poise) when it is melted while being heated at a rate of 4°C / min under a load of 1°C and extruded from a nozzle having an inner diameter of 1 mm and a length of 10 mm.
[0048] The liquid crystal polyester is preferably a wholly aromatic liquid crystal polyester having only repeating units derived from aromatic compounds.
[0049] It should be noted that the term "source" in this specification refers to a change in the chemical structure of a functional group that contributes to polymerization of a raw material monomer without causing other structural changes. The source here is a concept that also includes the case where a polymerizable derivative of a raw material monomer is used as the source.
[0050] Examples of polymerizable derivatives of compounds having a carboxyl group, such as aromatic hydroxycarboxylic acids and aromatic dicarboxylic acids, include esters obtained by converting a carboxyl group into an alkoxycarbonyl group or an aryloxycarbonyl group; acid halides obtained by converting a carboxyl group into a haloformyl group; and acid anhydrides obtained by converting a carboxyl group into an acyloxycarbonyl group.
[0051] Examples of polymerizable derivatives of compounds having a hydroxyl group such as aromatic hydroxycarboxylic acids, aromatic diols, and aromatic hydroxyamines include acylated products obtained by acylating a hydroxyl group to convert it into an acyloxy group.
[0052] Examples of polymerizable derivatives of compounds having an amino group such as aromatic hydroxyamine and aromatic diamine include acylated products obtained by acylation of an amino group to convert it into an acylamino group.
[0053] The liquid crystal polyester preferably contains a repeating unit including a naphthalene structure (hereinafter, also referred to as a repeating unit Z). By containing the repeating unit Z, the dielectric loss tangent of the liquid crystal polyester can be easily reduced.
[0054] The ratio of the content of the repeating unit Z based on the number of units may be 40% or more, 50% or more, 55% or more, or 60% or more relative to the total number of all repeating units in the liquid crystal polyester (100%). When the ratio of the content of the repeating unit Z is above the above lower limit, the dielectric loss tangent of the liquid crystal polyester can be further reduced.
[0055] The ratio of the content of the repeating unit Z in the liquid crystal polyester based on the number of units may be 90% or less, 85% or less, or 80% or less relative to the total number of all repeating units in the liquid crystal polyester (100%). When the ratio of the content of the repeating unit Z is below the above upper limit, the reaction stability during the production of the liquid crystal polyester can be ensured.
[0056] The content ratio of the repeating unit Z based on the number may be 40% to 90%, 50% to 85%, 55% to 85%, or 60% to 80%.
[0057] In the present specification, the "content of repeating units" of the liquid crystal polyester refers to the ratio of the total number of the repeating units to the total number of all repeating units of all liquid crystal polyesters contained in the liquid crystal polyester composition.
[0058] The number of repeating units in the liquid crystal polyester can be calculated based on the total value obtained by dividing the mass of each repeating unit constituting the liquid crystal polyester by the formula weight of each repeating unit to obtain the molar equivalent of each repeating unit.
[0059] When the liquid crystal polyester composition contains a plurality of types of liquid crystal polyesters, all the liquid crystal polyesters contain a form in which different types of liquid crystal polyesters are blended.
[0060] The liquid crystal polyester preferably has a repeating unit derived from a hydroxycarboxylic acid (hereinafter, also referred to as a repeating unit Y).
[0061] The ratio of the content of the repeating unit Y based on the number of units relative to the total number of all repeating units in the liquid crystal polyester of 100% may also be more than 50%, 55% or more, or 60% or more. The higher the content of the repeating unit Y, the less likely it is to produce an increase in viscosity caused by a drop in the temperature of the liquid crystal polyester composition, and the better the processing characteristics.
[0062] The ratio of the content of the repeating unit Y in the liquid crystal polyester based on the number of units may be 90% or less, 85% or less, or 80% or less relative to 100% of the total number of all repeating units in the liquid crystal polyester.
[0063] The content ratio of the repeating unit Y based on the number may be more than 50% and 90% or less, 55% or more and 85% or less, or 60% or more and 80% or less.
[0064] As preferred liquid crystal polyesters that may be contained in the liquid crystal polyester composition of the embodiment, the following liquid crystal polyester (A) and liquid crystal polyester (B) are exemplified.
[0065] The liquid crystal polyester composition of the embodiment may include the following liquid crystal polyester (A). By including the liquid crystal polyester (A), the dielectric loss tangent value of the liquid crystal polyester composition can be easily reduced.
[0066] The liquid crystal polyester composition of the embodiment may include the following liquid crystal polyester (B). By including the liquid crystal polyester (B), the processing characteristics of the liquid crystal polyester composition can be easily improved.
[0067] The liquid crystal polyester composition of the embodiment may contain the following liquid crystal polyester (A) and liquid crystal polyester (B). By containing the liquid crystal polyester (A) and the liquid crystal polyester (B), the dielectric loss tangent and the processing characteristics are well balanced.
[0068] In the liquid crystal polyester composition of the embodiment, “excellent processing characteristics” means that an increase in viscosity due to a decrease in the temperature of the liquid crystal polyester composition is unlikely to occur.
[0069] (Liquid Crystal Polyester (A))
[0070] The above-mentioned liquid crystal polyester (A) has:
[0071] A repeating unit represented by the following formula (A1) (hereinafter, also referred to as repeating unit (A1)), a repeating unit represented by the following formula (A2) (hereinafter, also referred to as repeating unit (A2)), and a repeating unit represented by the following formula (A3) (hereinafter, also referred to as repeating unit (A3)).
[0072] (A1)-O-Ar 1 -CO-
[0073] (A2)-CO-Ar 2 -CO-
[0074] (A3)-X 3 -Ar 3 -Y 3 -
[0075] (Ar 1 represents a phenylene group, a naphthylene group or a biphenylene group,
[0076] Ar 2 and Ar 3 Each independently represents a phenylene group, a naphthylene group, a biphenylene group or a group represented by the following formula (A4),
[0077] X 3 and Y 3 each independently represents an oxygen atom or an imino group (-NH-),
[0078] Ar 1 ,Ar 2 or Ar 3 The hydrogen atoms in the above groups represented may also be independently substituted by halogen atoms, alkyl groups or aryl groups.
[0079] (A4)-Ar 4 -Z-Ar 5 -
[0080] (Ar 4 and Ar 5 each independently represents a phenylene group or a naphthylene group,
[0081] Z represents an oxygen atom, a sulfur atom, a carbonyl group, a sulfonyl group or an alkylene group.)
[0082] As Ar in the above formula 1 ,Ar 2 or Ar 3 Examples of the halogen atom substituted for a hydrogen atom in the group represented by include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0083] Examples of the alkyl group having 1 to 10 carbon atoms which may be substituted with a hydrogen atom include methyl, ethyl, 1-propyl, isopropyl, 1-butyl, isobutyl, sec-butyl, tert-butyl, 1-hexyl, 2-ethylhexyl, 1-octyl and 1-decyl.
[0084] Examples of the aryl group having 6 to 20 carbon atoms which may be substituted with a hydrogen atom include monocyclic aromatic groups such as phenyl, o-tolyl, m-tolyl, p-tolyl, and the like, and ring-condensed aromatic groups such as 1-naphthyl, 2-naphthyl, and the like.
[0085] In Ar 1 ,Ar 2 , or Ar 3 When one or more hydrogen atoms in the above-mentioned group represented by is substituted by the above-mentioned halogen atom, the above-mentioned alkyl group having 1 to 10 carbon atoms, or the above-mentioned aryl group having 6 to 20 carbon atoms, the number of groups replacing the above-mentioned hydrogen atoms is 1 ,Ar 2 , or Ar 3 The groups represented may each independently be 1 or 2 or 1.
[0086] It should be noted that, when the liquid crystal polyester composition of the embodiment is required to have particularly good heat resistance, the number of groups replacing these hydrogen atoms is preferably small, and the number of groups replacing hydrogen atoms may be zero.
[0087] The liquid crystal polyester (A) preferably contains a repeating unit Z. By containing the repeating unit Z, the dielectric loss tangent of the liquid crystal polyester (A) can be easily reduced.
[0088] In the liquid crystal polyester (A) having repeating units (A1), repeating units (A2) and repeating units (A3), Ar 1 ,Ar 2 and Ar 3 At least one of them is preferably a naphthylene group, and more preferably a 2,6-naphthylene group.
[0089] In the liquid crystal polyester (A) containing repeating units Z, the ratio of the content of the repeating units Z based on the number of units relative to the total number of all repeating units in the liquid crystal polyester (A) of 100% may be 40% or more, 50% or more, 55% or more, or 60% or more. When the ratio of the content of the repeating units Z is above the above lower limit, the dielectric loss tangent of the liquid crystal polyester (A) can be further reduced.
[0090] In the liquid crystal polyester (A) containing repeating units Z, the content of the repeating units Z on a number basis may be 90% or less, 85% or less, or 80% or less relative to 100% of the total number of all repeating units in the liquid crystal polyester. When the content of the repeating units Z is below the above upper limit, the reaction stability during the production of the liquid crystal polyester (A) can be ensured.
[0091] The content ratio of the repeating unit Z mentioned above on a number basis may be 40% to 90%, 50% to 85%, 55% to 85%, or 60% to 80%.
[0092] The liquid crystal polyester (A) having the repeating unit (A1), the repeating unit (A2) and the repeating unit (A3) preferably has Ar 1 and / or Ar 2 It is a repeating unit of 2,6-naphthylene.
[0093] In the liquid crystal polyester (A) having repeating units (A1), repeating units (A2) and repeating units (A3), Ar 1 and / or Ar 2 The ratio of the content of the repeating units of 2,6-naphthylene based on the number of units may be 40% or more, 40% or more and 90% or less, 50% or more and 85% or less, 55% or more and 85% or less, or 60% or more and 80% or less, relative to 100% of the total number of all repeating units in the above-mentioned liquid crystal polyester (A).
[0094] The repeating unit (A1) is a repeating unit derived from an aromatic hydroxycarboxylic acid. Examples of the above-mentioned aromatic hydroxycarboxylic acid include p-hydroxybenzoic acid, m-hydroxybenzoic acid, 2-hydroxy-6-naphthoic acid, 2-hydroxy-3-naphthoic acid, 1-hydroxy-5-naphthoic acid, 4-hydroxy-4'-carboxy diphenyl ether, and aromatic hydroxycarboxylic acids in which a portion of the hydrogen atoms in the aromatic ring of these aromatic hydroxycarboxylic acids are substituted with a substituent selected from the group consisting of an alkyl group, an aryl group, and a halogen atom. The above-mentioned aromatic hydroxycarboxylic acids can be used alone or in combination in the manufacture of liquid crystal polyesters. As the repeating unit (A1), Ar is preferably 1 is a repeating unit of 1,4-phenylene (for example, a repeating unit derived from 4-hydroxybenzoic acid) and Ar 1 The repeating unit is a 2,6-naphthylene group (for example, a repeating unit derived from 6-hydroxy-2-naphthoic acid).
[0095] The repeating unit (A2) is a repeating unit derived from an aromatic dicarboxylic acid.
[0096] Examples of the aromatic dicarboxylic acid include terephthalic acid, isophthalic acid, biphenyl-4,4'-dicarboxylic acid, 2,6-naphthalene dicarboxylic acid, diphenyl ether-4,4'-dicarboxylic acid, diphenyl sulfide-4,4'-dicarboxylic acid, and aromatic dicarboxylic acids in which a portion of hydrogen atoms in the aromatic ring of these aromatic dicarboxylic acids are substituted with a substituent selected from the group consisting of an alkyl group, an aryl group, and a halogen atom. The aromatic dicarboxylic acids may be used alone or in combination in the manufacture of the liquid crystal polyester.
[0097] As the repeating unit (A2), Ar 2 is a repeating unit of 1,4-phenylene (for example, a repeating unit derived from terephthalic acid), Ar 2 is a repeating unit of 1,3-phenylene (for example, a repeating unit derived from isophthalic acid), Ar 2 is a repeating unit of 2,6-naphthylene (for example, a repeating unit derived from 2,6-naphthalenedicarboxylic acid) and Ar 2 It is a repeating unit of diphenyl ether-4,4'-diyl (for example, a repeating unit derived from diphenyl ether-4,4'-dicarboxylic acid).
[0098] The repeating unit (A3) is a repeating unit derived from an aromatic diol, an aromatic hydroxyamine or an aromatic diamine.
[0099] Examples of the aromatic diol, aromatic hydroxyamine or aromatic diamine include 4,4'-dihydroxybiphenyl, hydroquinone, methylhydroquinone, resorcinol, 4,4'-dihydroxydiphenyl ketone, 4,4'-dihydroxydiphenyl ether, bis(4-hydroxyphenyl)methane, 1,2-bis(4-hydroxyphenyl)ethane, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl sulfide, 2,6-dihydroxynaphthalene, 1,5-dihydroxynaphthalene, 4-aminophenol, 1,4-phenylenediamine, 4-amino-4'-hydroxybiphenyl and 4,4'-diaminobiphenyl.
[0100] The above-mentioned aromatic diol, aromatic hydroxyamine or aromatic diamine may be used alone or in combination of two or more kinds in the production of the liquid crystal polyester.
[0101] As the repeating unit (A3), Ar 3 is a repeating unit of 1,4-phenylene (for example, a repeating unit derived from hydroquinone, 4-aminophenol or 1,4-phenylenediamine) and Ar 3 The repeating unit is a 4,4'-biphenylene group (for example, a repeating unit derived from 4,4'-dihydroxybiphenyl, 4-amino-4'-hydroxybiphenyl or 4,4'-diaminobiphenyl).
[0102] The ratio of the content of the repeating unit (A1) in the liquid crystal polyester (A) based on the number of units may be 30% to 80%, 40% to 70%, or 45% to 65% relative to 100% of the total number of all repeating units.
[0103] The ratio of the content of the repeating units (A2) in the liquid crystal polyester (A) based on the number of units may be 35% or less, 10% or more and 35% or less, 15% or more and 30% or less, or 17.5% or more and 27.5% or less, relative to 100% of the total number of all repeating units.
[0104] The ratio of the content of the repeating units (A3) in the liquid crystal polyester (A) on a number basis to the total number of all repeating units (100%) may be 35% or less, 10% or more and 35% or less, 15% or more and 30% or less, or 17.5% or more and 27.5% or less.
[0105] The higher the content ratio of the repeating unit (A1) in the liquid crystal polyester (A), the easier it is to improve the melt fluidity and heat resistance of the liquid crystal polyester, and the strength and rigidity of the molded product. However, if it is too much, the melting temperature and melt viscosity of the liquid crystal polyester are likely to increase, and the temperature required for molding is likely to increase.
[0106] The ratio of the content of the repeating unit (A2) to the content of the repeating unit (A3) in the liquid crystal polyester (A) ([content of the repeating unit (A2)] / [content of the repeating unit (A3)] (number / number)) may be 0.9 / 1 to 1 / 0.9, 0.95 / 1 to 1 / 0.95, or 0.98 / 1 to 1 / 0.98.
[0107] It should be noted that the liquid crystal polyester (A) may also independently have two or more repeating units (A1), repeating units (A2) and repeating units (A3). The liquid crystal polyester may also have repeating units other than the repeating units (A1), repeating units (A2) and repeating units (A3), but the content ratio thereof may be less than 10%, less than 5%, or 0% based on the total number of all repeating units constituting the liquid crystal polyester (A), which is 100%.
[0108] In the liquid crystal polyester (A) comprising the repeating unit (A1), the repeating unit (A2) and the repeating unit (A3), the sum of the content of the repeating unit (A1), the content of the repeating unit (A2) and the content of the repeating unit (A3) does not exceed 100% on a number basis.
[0109] In this specification, the number of each repeating unit of the liquid crystal polyester is determined by the analysis method described in Japanese Patent Application Laid-Open No. 2000-19168.
[0110] The number of each repeating unit relative to all repeating units can be calculated by reacting the liquid crystal polyester with a lower alcohol in a supercritical state to depolymerize it, and then quantifying the depolymerization product (monomer from which each repeating unit is derived) by liquid chromatography.
[0111] For example, when the liquid crystal polyester is composed of a repeating unit (A1), a repeating unit (A2) and a repeating unit (A3), the number of the repeating unit (A1) can be determined by the following method: the molar concentrations of monomers from which the repeating unit (A1), the repeating unit (A2) and the repeating unit (A3) are respectively derived are calculated by liquid chromatography, and the ratio of the molar concentration of the monomer from which the repeating unit (A1) is calculated when the total molar concentration of the monomers from which the repeating unit (A1), the repeating unit (A2) and the repeating unit (A3) are respectively derived is set to 100%.
[0112] From the viewpoint of reducing dielectric loss tangent, the liquid crystal polyester (A) preferably has a repeating unit represented by the following formula (A1-1), a repeating unit represented by the following formula (A2-1), and a repeating unit represented by the following formula (A3-1).
[0113] (A1-1)-O-Ar 1-1 -CO-
[0114] (A2-1)-CO-Ar 2-1 -CO-
[0115] (A3-1)-O-Ar 3-1 -O-
[0116] (Ar 1-1 ,Ar 2-1 and Ar 3-1 each independently represents a phenylene group, a naphthylene group, or a biphenylene group,
[0117] Ar 1-1 ,Ar 2-1 or Ar 3-1 The hydrogen atoms in the above groups represented may also be independently substituted by halogen atoms, alkyl groups, or aryl groups.
[0118] About Ar 1-1 ,Ar 2-1 and Ar 3-1 Related specific examples and preferred solutions can be found in Ar 1-1 ,Ar 2-1 and Ar 3-1 The definition of Ar is applied within the scope of the above1 ,Ar 2 and Ar 3 Specific examples and preferred embodiments are described.
[0119] From the viewpoint of reducing dielectric loss tangent, the liquid crystal polyester (A) preferably has a repeating unit represented by the following formula (A1-2), a repeating unit represented by the following formula (A2-2), and a repeating unit represented by the following formula (A3-2).
[0120] (A1-2)-O-Ar 1-2 -CO-
[0121] (A2-2)-CO-Ar 2-2 -CO-
[0122] (A3-2)-O-Ar 3-2 -O-
[0123] (Ar 1-2 represents 2,6-naphthylene, 1,4-phenylene, or 4,4'-biphenylene,
[0124] Ar 2-2 and Ar 3-2 each independently represents a 2,6-naphthylene group, a 2,7-naphthylene group, a 1,4-phenylene group, a 1,3-phenylene group, or a 4,4′-biphenylene group,
[0125] Ar 1-2 ,Ar 2-2 or Ar 3-2 The hydrogen atoms in the above groups represented may be substituted independently by a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0126] About Ar 1-2 ,Ar 2-2 and Ar 3-2 Related specific examples and preferred solutions can be found in Ar 1-2 ,Ar 2-2 and Ar 3-2 The definition of Ar is applied within the scope of the above 1 ,Ar 2 and Ar 3 Specific examples and preferred embodiments are described.
[0127] (Liquid crystal polyester (B))
[0128] The liquid crystal polyester (B) has a repeating unit represented by the following formula (B1) (hereinafter, also referred to as a repeating unit (B1)).
[0129] (B1)-O-Ar b1 -CO-
[0130] (Ar b1 represents a phenylene group, a naphthylene group or a biphenylene group,
[0131] Ar b1 The hydrogen atoms in the above groups represented may also be independently substituted by halogen atoms, alkyl groups or aryl groups.
[0132] As the above Ar b1 The phenylene group, naphthylene group and biphenylene group in the above-mentioned liquid crystal polyester (A) can be exemplified.
[0133] As Ar b1 The halogen atom and the alkyl group or aryl group in the above-mentioned group may be the same as those exemplified in the above-mentioned liquid crystal polyester (A).
[0134] In the liquid crystal polyester (B), as the content of the repeating unit (B1) increases, the viscosity increase caused by the temperature drop of the liquid crystal polyester composition can be further suppressed.
[0135] From the above viewpoint, the content of the repeating unit (B1) may be more than 80% based on the number of the total number of all repeating units of the liquid crystal polyester (B), or may be 85% or more and 100% or less, or 90% or more and 100% or less, or 95% or more and 100% or less, or 98% or more and 100% or less. The liquid crystal polyester (B) may be substantially composed of the repeating unit (B1), i.e., the content of the repeating unit (B1) is 100%.
[0136] From the viewpoint of further suppressing the increase in viscosity caused by a decrease in the temperature of the liquid crystal polyester composition, the liquid crystal polyester (B) is
[0137] The repeating unit (B1) preferably contains a repeating unit represented by the following formula (B1-1).
[0138] (B1-1)-O-Ar b1-1 -CO-
[0139] (Ar b1-1 represents naphthylene,
[0140] Ar b1-1 The hydrogen atoms in the above groups represented may also be independently substituted by halogen atoms, alkyl groups or aryl groups.
[0141] The content of the repeating unit represented by the above formula (B1-1) (hereinafter also referred to as repeating unit (B1-1)) may be more than 50% and less than 90% or 65 to 80% based on the number of units relative to 100% of the total number of repeating units (B1).
[0142] In the liquid crystal polyester (B), when the content ratio of the repeating unit (B1-1) is within the above range, the viscosity increase caused by the temperature drop of the liquid crystal polyester composition can be further suppressed, and a low dielectric loss tangent can be exhibited.
[0143] In the liquid crystal polyester (B), the repeating unit (B1) may contain the repeating unit (B1-1) and a repeating unit represented by the following formula (B1-2) (hereinafter also referred to as the repeating unit (B1-2)), or may consist only of the repeating unit (B1-1) and the repeating unit (B1-2).
[0144] (B1-1)-O-Ar b1-1 -CO-
[0145] (B1-2)-O-Ar b1-2 -CO-
[0146] (Ar b1-1 represents naphthylene,
[0147] Ar b1-2 represents phenylene,
[0148] Ar b1-1 or Ar b1-2 The hydrogen atoms in the above groups represented may also be independently substituted by halogen atoms, alkyl groups or aryl groups.
[0149] As the above Ar b1-1 Examples of the naphthylene group in include the groups exemplified in the above-mentioned liquid crystal polyester (A).
[0150] As the above Ar b1-2 The phenylene group in the above-mentioned liquid crystal polyester (A) can be exemplified.
[0151] As Ar b1-1 and Ar b1-2 The halogen atom, alkyl group or aryl group in can be exemplified by the groups exemplified in the above-mentioned liquid crystal polyester (A).
[0152] The repeating unit (B1) is a repeating unit derived from an aromatic hydroxycarboxylic acid. Examples of the repeating unit derived from an aromatic hydroxycarboxylic acid include the repeating units exemplified as the repeating unit (A1).
[0153] When the repeating unit (B1) includes the repeating unit (B-1) and the repeating unit (B1-2), the content of the repeating unit (B1-1) may be more than 50% and less than 90% based on the number of units relative to 100% of the total number of all repeating units of the liquid crystal polyester (B),
[0154] The content of the repeating unit (B1-2) is 10% or more and less than 50%,
[0155] The content of the repeating unit (B1-1) may be 65% or more and 80% or less.
[0156] And the content ratio of the repeating unit (B1-2) is 20% or more and 35% or less.
[0157] It should be noted that the liquid crystal polyester (B) may have two or more repeating units (B1) independently. The liquid crystal polyester (B) may also have repeating units other than the repeating unit (B1), but the content ratio thereof may be less than 10%, less than 5%, or 0% based on the total number of all repeating units of the liquid crystal polyester (B) (100%).
[0158] The liquid crystal polyester (B) may also be composed only of the repeating unit (B1), and the repeating unit (B1) may also include the repeating unit represented by the following formula (B1-1-1) and the repeating unit represented by the formula (B1-2-1), or may be composed only of the repeating unit represented by the following formula (B1-1-1) and the repeating unit represented by the formula (B1-2-1).
[0159] (B1-1-1)-O-Ar b1-1-1 -CO-
[0160] (B1-2-1)-O-Ar b1-2-1 -CO-
[0161] (Ar b1-1-1 represents 2,6-naphthylene,
[0162] Ar b1-2-1 represents 1,4-phenylene,
[0163] Ar b1-1-1 or Ar b1-2-1 The hydrogen atoms in the above groups represented may be substituted independently by a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0164] As particularly preferred combinations of the liquid crystal polyester (A) and the liquid crystal polyester (B) exemplified above, there can be mentioned:
[0165] The liquid crystal polyester (A) is a liquid crystal polyester having the following repeating unit (A1-3), the following repeating unit (A2-3) and the following repeating unit (A3-3),
[0166] (A1-3)-O-Ar 1-3 -CO-
[0167] (A2-3)-CO-Ar 2-3 -CO-
[0168] (A3-3)-O-Ar 3-3 -O-
[0169] (Ar 1-3 represents 2,6-naphthylene,
[0170] Ar 2-3 and Ar 3-3 Each independently represents a 2,6-naphthylene group or a 1,4-phenylene group,
[0171] Ar 1-3 ,Ar 2-3 or Ar 3-3 The hydrogen atoms in the above groups represented may be substituted independently by a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0172] The liquid crystal polyester (B) is a liquid crystal polyester consisting only of the repeating unit (B1-1-1) and the repeating unit (B1-2-1).
[0173] (B1-1-1)-O-Ar b1-1-1 -CO-
[0174] (B1-2-1)-O-Ar b1-2-1 -CO-
[0175] (Ar b1-1-1 represents 2,6-naphthylene,
[0176] Ar b1-2-1 represents 1,4-phenylene,
[0177] Ar b1-1-1 or Ar b1-2-1 The hydrogen atoms in the above groups represented may be substituted independently by a halogen atom, an alkyl group having 1 to 10 carbon atoms, or an aryl group having 6 to 20 carbon atoms.
[0178] When the above-mentioned liquid crystal polyester composition contains the above-mentioned liquid crystal polyester (A) and the above-mentioned liquid crystal polyester (B), from the viewpoint of an excellent balance between low dielectric loss tangent and good processing characteristics, the ratio (mass ratio) of the content of the above-mentioned liquid crystal polyester (A) to the above-mentioned liquid crystal polyester (B) in the above-mentioned liquid crystal polyester composition may be liquid crystal polyester (A) / liquid crystal polyester (B) = 95 / 5 to 50 / 50, 95 / 5 to 50 / 50 (except 50 / 50), 90 / 10 to 60 / 40, or 60 / 40.
[0179] From the viewpoint of further improving the mechanical strength in addition to the above, the content ratio of the liquid crystal polyester (A) to the liquid crystal polyester (B) may be liquid crystal polyester (A) / liquid crystal polyester (B) = 80 / 20 to 60 / 40 by mass, or 60 / 40.
[0180] The total content of the liquid crystal polyester (A) and the liquid crystal polyester (B) may be 50% by mass or more, 80% by mass or more, or 100% by mass based on 100% by mass of the total mass of the liquid crystal polyester in the liquid crystal polyester composition of the embodiment.
[0181] The weight average molecular weight (Mw) of the liquid crystal polyester which may be contained in the liquid crystal polyester composition may be 50,000 or more, 100,000 or more, or 200,000 or more.
[0182] The weight average molecular weight (Mw) of the liquid crystal polyester which may be contained in the liquid crystal polyester composition may be 1,000,000 or less, 700,000 or less, or 500,000 or less.
[0183] The weight average molecular weight (Mw) of the liquid crystal polyester which may be contained in the liquid crystal polyester composition may be in the above numerical range of 50,000 to 1,000,000, 100,000 to 700,000 or less, or 200,000 to 500,000.
[0184] When the weight average molecular weight of the liquid crystal polyester is below the above upper limit, the processing characteristics of the liquid crystal polyester composition become better. When the weight average molecular weight of the liquid crystal polyester is above the above lower limit, the molded product exhibits further good mechanical strength.
[0185] The number average molecular weight (Mn) of the liquid crystal polyester which may be contained in the liquid crystal polyester composition may be 1,000 or more, 5,000 or more, or 7,000 or more.
[0186] The number average molecular weight (Mn) of the liquid crystal polyester which may be contained in the liquid crystal polyester composition may be 500,000 or less, 300,000 or less, or 100,000 or less.
[0187] The number average molecular weight (Mn) of the liquid crystal polyester which may be contained in the liquid crystal polyester composition may be 1,000 to 500,000, 5,000 to 300,000 or less, or 7,000 to 100,000.
[0188] When the number average molecular weight of the liquid crystal polyester is below the above upper limit, the processing characteristics of the liquid crystal polyester composition become better. When the number average molecular weight of the liquid crystal polyester is above the above lower limit, the molded product exhibits further good mechanical strength.
[0189] The polydispersity (Mw / Mn) of the liquid crystal polyester in the liquid crystal polyester composition is not particularly limited, but can be exemplified by 1.0 to 4.0.
[0190] In this specification, the “weight average molecular weight” and “number average molecular weight” can be determined by gel permeation chromatography (GPC) analysis, and refer to values determined in terms of standard polystyrene based on a calibration curve obtained by measuring the molecular weight of standard polystyrene.
[0191] (Method for producing liquid crystal polyester)
[0192] The liquid crystal polyester is preferably produced by melt-polymerizing the raw material monomers corresponding to the repeating units contained therein and, if necessary, solid-phase polymerizing the resulting polymer. Thus, a high molecular weight liquid crystal polyester that can be molded into a molded body having high heat resistance, strength, and rigidity can be produced with good operability.
[0193] Melt polymerization can also be carried out in the presence of a catalyst. Examples of the catalyst include metal compounds such as magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, antimony trioxide, and nitrogen-containing heterocyclic compounds such as 4-(dimethylamino)pyridine and 1-methylimidazole. Preferably, nitrogen-containing heterocyclic compounds are used.
[0194] <Olefin Copolymer>
[0195] The olefin-based copolymer contained in the liquid crystal polyester composition of the present embodiment is a copolymer including a repeating unit A derived from an olefin monomer having 2 to 8 carbon atoms and a repeating unit B having a glycidyl group.
[0196] The olefin-based copolymer may be a copolymer having a main chain including repeating units A and B.
[0197] The repeating unit A may be a repeating unit derived from ethylene, a repeating unit derived from an α-olefin, a repeating unit derived from a cyclic olefin, a repeating unit derived from an aromatic olefin, or a combination thereof. Examples of α-olefins include 1-butene, 1-pentene, 1-hexene, 1-heptene, and 1-octene, examples of cyclic olefins include norbornene, 5-methylnorbornene, and 1-methylnorbornene, and examples of aromatic olefins include styrene, methylstyrene, and divinylbenzene.
[0198] The content ratio of the repeating unit A in the above-mentioned olefin-based copolymer (preferably the total ratio of the repeating unit derived from ethylene and the repeating unit derived from α-olefin) can be 80% by mass or more, 90% by mass or more, more than 94% by mass, 94.5% by mass or more, 95% by mass or more, 96% by mass or more, 97% by mass or more, or 97.5% by mass or more, relative to the total mass of the olefin-based copolymer (100% by mass). The ratio of the repeating unit A (preferably the total ratio of the repeating unit derived from ethylene and the repeating unit derived from α-olefin) can also be 99.9% by mass or less, 99.5% by mass or less, 99% by mass or less, or 98% by mass or less, relative to the total mass of the olefin-based copolymer (100% by mass).
[0199] The proportion of repeating units A (preferably the total proportion of repeating units derived from ethylene and repeating units derived from α-olefins) relative to the total mass of the olefin-based copolymer (100 mass%) can be 80 mass% or more and 99.9 mass% or less, can be 90 mass% or more and 99.5 mass% or less, can be 93 mass% or more and 99 mass% or less, can be 93 mass% or more and 98 mass% or less, can be more than 94 mass% and 99 mass% or less, can be 94.5 mass% or more and 98 mass% or less, can be 97 mass% or more and 98 mass% or less.
[0200] When the ratio of the content of the repeating unit A is not less than the above lower limit, the liquid crystal polyester composition can be prevented from becoming sticky, and the handling during the production of the liquid crystal polyester composition and the production efficiency of a molded product are good.
[0201] When the ratio of the content of the repeating unit A is below the above upper limit, the modification effect due to the inclusion of the repeating unit B etc. can be effectively imparted.
[0202] Repeating unit B may be a repeating unit derived from an unsaturated carboxylic acid glycidyl ester, may be a repeating unit derived from a glycidyl ether having an unsaturated group, or may be a combination thereof. Repeating unit B is preferably present at least in the main chain of the olefin-based copolymer. Repeating unit B may also not be present at the end of the olefin-based copolymer.
[0203] The unsaturated carboxylic acid glycidyl ester may also be a compound represented by the following formula (I). 1 represents an alkenyl group having 2 to 18 carbon atoms, and the alkenyl group may have one or more substituents. Examples of the compound represented by formula (I) include glycidyl acrylate, glycidyl methacrylate, and glycidyl itaconate.
[0204] [Chemical formula 1]
[0205]
[0206] The glycidyl ether having an unsaturated group may also be a compound represented by the following formula (II). 2 represents an alkenyl group having 2 to 18 carbon atoms, which may have one or more substituents. X represents CH2-O (CH2 and R 2 Examples of the compound represented by formula (II) include allyl glycidyl ether, 2-methylallyl glycidyl ether, and styrene p-glycidyl ether.
[0207] [Chemical formula 2]
[0208]
[0209] It is presumed that the olefin-based copolymer including the repeating unit B improves compatibility with the liquid crystal polyester, and further causes a reaction between the terminal group (eg, hydroxyl group, carboxyl group, etc.) of the liquid crystal polyester and the glycidyl group.
[0210] The content ratio of the repeating unit B in the above-mentioned olefin-based copolymer can be 0.1% by mass or more, 0.5% by mass or more, 1% by mass or more, 1.5% by mass or more, 2% by mass or more, or 2.2% by mass or more, relative to the total mass 100% by mass of the olefin-based copolymer. The content ratio of the repeating unit B can be 20% by mass or less, 10% by mass or less, less than 6% by mass, 5.5% by mass or less, 5% by mass or less, 4% by mass or less, 3.5% by mass or less, 3% by mass or less, 2.5% by mass or less, or 2.3% by mass or less, based on the mass of the olefin-based copolymer.
[0211] The ratio of the content of the repeating unit B in the above-mentioned olefin-based copolymer, relative to the total mass of the olefin-based copolymer (100 mass%), can be 0.1 mass% to 20 mass%, can be 0.5 mass% to 10 mass%, can be 1 mass% to 7 mass%, can be 2 mass% to 7 mass%, can be 1 mass% to less than 6 mass%, can be 2 mass% to 5.5 mass%, or can be 2 mass% to 3 mass%.
[0212] When the ratio of the content of the repeating unit B is not less than the above lower limit, the above-mentioned function of the glycidyl group is likely to be well exerted.
[0213] When the ratio of the content of the repeating unit B is equal to or less than the above upper limit, the melt viscosity of the liquid crystal polyester composition is unlikely to become too high, and the dielectric loss tangent is unlikely to become too high.
[0214] The content ratio of the repeating unit A and the repeating unit B exemplified above can be appropriately combined within the range where the sum of the contents does not exceed 100% by mass.
[0215] From the viewpoint of an excellent balance between the effect of the glycidyl group and the melt viscosity and dielectric loss tangent of the liquid crystal polyester composition, the repeating unit A may be 80% by mass or more and 99.9% by mass or less, and the repeating unit B may be 0.1% by mass or more and 20% by mass or less, the repeating unit A may be 90% by mass or more and 99.5% by mass or less, and the repeating unit B may be 0.5% by mass or more and 10% by mass or less, or the repeating unit A may be 93% by mass or more and 99% by mass or less, and the repeating unit B may be 0.1% by mass or more and 20% by mass or less, relative to the total mass of the olefin-based copolymer (100% by mass). The composition of the present invention can be from 1 mass % to 7 mass %, or the repeating unit A can be from 93 mass % to 98 mass %, and the repeating unit B can be from 2 mass % to 7 mass %, or the repeating unit A can be more than 94 mass % and less than 99 mass %, and the repeating unit B can be from 1 mass % to less than 6 mass %, or the repeating unit A can be from 94.5 mass % to 98 mass %, and the repeating unit B can be from 2 mass % to 5.5 mass %, or the repeating unit A can be from 97 mass % to 98 mass %, and the repeating unit B can be from 2 mass % to 3 mass %.
[0216] The mass ratio of repeating unit B to repeating unit A (ratio of repeating unit B / ratio of repeating unit A) may be 0.001 or more, 0.005 or more, 0.01 or more, 0.015 or more, or 0.02 or more. The mass ratio of repeating unit B to repeating unit A (ratio of repeating unit B / ratio of repeating unit A) may be 0.06 or less, 0.05 or less, 0.04 or less, 0.03 or less, or 0.025 or less. The mass ratio of repeating unit B to repeating unit A (ratio of repeating unit B / ratio of repeating unit A) may be 0.001 to 0.06, or 0.005 to 0.05.
[0217] The olefin-based copolymer preferably has a main chain that further contains a repeating unit C derived from (meth)acrylate or vinyl ether (except for the repeating unit corresponding to the repeating unit B. Hereinafter, it is also referred to as repeating unit C). "(Meth)acrylate" refers to acrylate or methacrylate, and the same applies to similar compounds.
[0218] Examples of (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, and butyl (meth)acrylate. Examples of vinyl ethers include methyl vinyl ether, ethyl vinyl ether, propyl vinyl ether, and phenyl vinyl ether.
[0219] The content of repeating unit C may be 3% or less, 2% or less, 1% or less, lower than 1% or less, 0.5% or less, or 0.1% or less, relative to the total mass 100% by mass of the olefin copolymer. The content of repeating unit C may be 0% by mass, based on the mass of the olefin copolymer.
[0220] When the olefin-based copolymer contains repeating units C, the ratio of the total content of repeating units B and repeating units C can be exemplified by the same numerical values as exemplified as the ratio of the content of repeating units B in the above-mentioned olefin-based copolymer.
[0221] The mass ratio of repeating unit C to repeating unit B (ratio of repeating unit C / ratio of repeating unit B) may be 0.1 or less, 0.05 or less, or 0.01 or less. The mass ratio of repeating unit C to repeating unit B (ratio of repeating unit C / ratio of repeating unit B) may be 0.
[0222] Examples of olefin copolymers include ethylene-glycidyl (meth)acrylate copolymers, ethylene-glycidyl (meth)acrylate-methyl (meth)acrylate copolymers, ethylene-glycidyl (meth)acrylate-ethyl (meth)acrylate copolymers, ethylene-glycidyl (meth)acrylate-n-propyl (meth)acrylate copolymers, ethylene-glycidyl (meth)acrylate-isopropyl (meth)acrylate copolymers, ethylene-glycidyl (meth)acrylate-n-butyl (meth)acrylate copolymers, ethylene-glycidyl (meth)acrylate-isobutyl (meth)acrylate copolymers, and ethylene-glycidyl (meth)acrylate-vinyl ether copolymers. The olefin copolymer may also be an ethylene-glycidyl (meth)acrylate copolymer.
[0223] Olefin copolymers can be synthesized by various methods. For example, olefin copolymers can be produced by bulk polymerization, emulsion polymerization, solution polymerization, etc. using a free radical initiator. An example of a representative polymerization method for synthesizing olefin copolymers is to perform polymerization in the presence of a polymerization initiator that generates free radicals at a polymerization pressure of 500 kg / cm 2The above method is a method of copolymerizing an olefin monomer having 2 to 8 carbon atoms, a monomer having a glycidyl group, and (meth)acrylate or vinyl ether as required at a polymerization temperature of 40 to 300°C. The polymerization pressure may also be 1000 kg / cm 2 Above, can also be 2000kg / cm 2 The polymerization temperature may be 100 to 250° C. or 150 to 200° C. When the olefin monomer having 2 to 8 carbon atoms, the monomer having a glycidyl group, and (meth)acrylate or vinyl ether used as required are randomly copolymerized, the olefin monomer having 2 to 8 carbon atoms and the monomer having a glycidyl group also exist in the main chain.
[0224] The melt flow rate (MFR) of the olefin copolymer may be 0.2 g / 10 minutes or more, 0.5 g / 10 minutes or more, 1 g / 10 minutes or more, 1.5 g / 10 minutes or more, 2 g / 10 minutes or more, 2.5 g / 10 minutes or more, or 3 g / 10 minutes or more. The melt flow rate (MFR) of the olefin copolymer may be 400 g / 10 minutes or less, 250 g / 10 minutes or less, 220 g / 10 minutes or less, or 200 g / 10 minutes or less.
[0225] The MFR of the above-mentioned olefin copolymer may be 0.2 g / 10 minutes or more, 0.5 g / 10 minutes or more and 400 g / 10 minutes or less, 1 g / 10 minutes or more and 400 g / 10 minutes or less, 1.5 g / 10 minutes or more and 400 g / 10 minutes or less, 2 g / 10 minutes or more and 250 g / 10 minutes or less, 2.5 g / 10 minutes or more and 220 g / 10 minutes or less, or 3 g / 10 minutes or more and 200 g / 10 minutes or less. The MFR of the olefin copolymer may be measured under the conditions of a temperature of 190° C. and a load of 2.16 kgf in accordance with JIS K7210.
[0226] <Optional Ingredients>
[0227] The liquid crystal polyester composition of the present embodiment may further contain optional components other than the above-mentioned liquid crystal polyester and olefin-based copolymer.
[0228] The liquid crystal polyester composition of the embodiment may contain a liquid crystal polyester, an olefin-based copolymer, and other optional components as needed such that the total content (mass %) of the liquid crystal polyester composition does not exceed the total mass (100 mass %) of the liquid crystal polyester composition of the embodiment.
[0229] Optional components include fillers, resins other than the above-mentioned liquid crystal polyesters and olefin copolymers, flame retardants, conductive materials, crystal nuclei, ultraviolet absorbers, antioxidants, vibration dampers, antibacterial agents, insect repellents, deodorants, anti-colorants, heat stabilizers, mold release agents, antistatic agents, plasticizers, lubricants, dyes, foaming agents, foam inhibitors, viscosity modifiers and surfactants.
[0230] (Composition / Physical Properties)
[0231] From the viewpoint of easily exerting the characteristics of the liquid crystal polyester, the ratio of the content of the above-mentioned liquid crystal polyester to the above-mentioned olefin-based copolymer in the liquid crystal polyester composition of the embodiment can be, by mass ratio, liquid crystal polyester / olefin-based copolymer = 99.9 / 0.1 to 50 / 50, can be 99.5 / 0.5 to 70 / 30, can be 99 / 1 to 80 / 20, or can be 97 / 3 to 90 / 10.
[0232] From the viewpoint of easily exerting the characteristics of the liquid crystal polyester, the content of the above-mentioned liquid crystal polyester relative to the total mass 100 mass % of the liquid crystal polyester composition of the embodiment can be 50 mass % or more, 80 mass % or more, 90 mass % or more, or 95 mass % or more.
[0233] The content of the liquid crystal polyester relative to 100% by mass of the total mass of the liquid crystal polyester composition of the embodiment may be appropriately determined in consideration of the content of the olefin copolymer, etc., and may be 99.9% by mass or less, 99% by mass or less, or 97% by mass or less.
[0234] The content of the above-mentioned liquid crystal polyester relative to the total mass (100 mass%) of the liquid crystal polyester composition of the embodiment can be 50 mass% or more and 99.9 mass% or less, 80 mass% or more and 99.9 mass% or less, 85 mass% or more and 99 mass% or less, 90 mass% or more and 99 mass% or more, 90 mass% or more and 97 mass% or more, or 95 mass% or more and 97 mass% or less.
[0235] From the viewpoint of preventing an excessive increase in the dielectric loss tangent of the liquid crystal polyester composition from occurring, the content of the olefin-based copolymer relative to 100% by mass of the total mass of the liquid crystal polyester composition of the embodiment may be 50% by mass or less, 20% by mass or less, 15% by mass or less, 12% by mass or less, 10% by mass or less, or 5% by mass or less.
[0236] From the viewpoint of further improving the heat resistance and tensile elongation of the liquid crystal polyester composition, the content of the above-mentioned olefin-based copolymer relative to 100% by mass of the total mass of the liquid crystal polyester composition of the embodiment can be 0.1% by mass or more, 1% by mass or more, 3% by mass or more, 5% by mass or more, or 8% by mass or more.
[0237] The content of the above-mentioned olefin-based copolymer relative to 100% by mass of the total mass of the liquid crystal polyester composition of the embodiment can be 0.1% by mass or more and 50% by mass or less, 0.1% by mass or more and 20% by mass or less, 1% by mass or more and 15% by mass or less, 1% by mass or more and 10% by mass or less, 3% by mass or more and 10% by mass or more, 3% by mass or more and 5% by mass or less, 5% by mass or more and 10% by mass or less, or 8% by mass or more and 12% by mass or less.
[0238] The numerical values of the ratios of the contents of the liquid crystal polyester and the olefin copolymer exemplified above can be appropriately combined within the range where their sum does not exceed 100% on a mass basis. As an example, relative to the total mass of the liquid crystal polyester composition of the embodiment (100 mass%), the liquid crystal polyester may be 50 mass% to 99.9 mass%, and the olefin copolymer may be 0.1 mass% to 50 mass%, or the liquid crystal polyester may be 80 mass% to 99.9 mass%, and the olefin copolymer may be 0.1 mass% to 20 mass%, or the liquid crystal polyester may be 85 mass% to 99 mass%, and the olefin copolymer may be 1 mass% to 15 mass%, or the liquid crystal polyester may be 90 mass% to 99 mass%, and the olefin copolymer may be 1 mass% to 20 mass%. The hydrocarbon copolymer may be from 1% to 10% by mass, the liquid crystal polyester may be from 90% to 97% by mass, and the olefin copolymer may be from 3% to 10% by mass, the liquid crystal polyester may be from 95% to 97% by mass, and the olefin copolymer may be from 3% to 5% by mass, the liquid crystal polyester may be from 90% to 95% by mass, and the olefin copolymer may be from 5% to 10% by mass, or the liquid crystal polyester may be from 88% to 92% by mass, and the olefin copolymer may be from 8% to 12% by mass.
[0239] The flow start temperature of the liquid crystal polyester composition of the embodiment may be 260° C. or higher, may exceed 271° C., or may be 280° C. or higher.
[0240] The upper limit of the flow start temperature of the liquid crystal polyester composition of the embodiment is not particularly limited, but the flow start temperature may be 400°C or less, or 380°C or less. The flow start temperature of the liquid crystal polyester composition of the embodiment may be 260°C or more and 400°C or less, may be more than 271°C or more and 380°C or less, or may be 280°C or more and 380°C or less.
[0241] The higher the flow start temperature of the liquid crystal polyester composition, the higher the heat resistance of the liquid crystal polyester composition, and the higher the strength of the molded body molded from the composition. On the other hand, if the flow start temperature of the liquid crystal polyester composition exceeds 400°C, the melting temperature and melt viscosity of the liquid crystal polyester composition tend to increase. Therefore, the temperature required for molding the liquid crystal polyester composition tends to increase.
[0242] In the present specification, the flow initiation temperature of the liquid crystal polyester composition can be obtained by measuring the flow initiation temperature of the liquid crystal polyester in the measurement method exemplified above using the liquid crystal polyester composition as a sample instead of the liquid crystal polyester.
[0243] The liquid crystal polyester composition of the embodiment has improved heat resistance by containing the above-mentioned olefin-based copolymer.
[0244] The heat resistance of the liquid crystal polyester composition of the embodiment can be evaluated by the following measurement method. In the above measurement, solder heat resistance can be evaluated.
[0245] 〔Solder heat resistance test〕
[0246] An injection molding machine (e.g., PNX-40-5A manufactured by Nissei Plastic Industry Co., Ltd.) was used to manufacture a molded product formed of the liquid crystal polyester composition, i.e., a dumbbell test piece (thickness 1.2 mm) of JIS K7113 (1 / 2) number, at a barrel temperature of 315 to 320°C, a mold temperature of 130°C, and an injection speed of 75 mm / s. The liquid crystal polyester composition was used as a molding material. The obtained dumbbell test piece was immersed in a solder bath (e.g., "L20" Sn / Bi=42 / 58 manufactured by Senju Metal Industry Co., Ltd.) heated to a specified temperature for 60 seconds, and after being taken out, it was visually confirmed whether blisters were seen on the surface of the above test piece. The temperature of the solder bath was increased by 5°C each time and the same evaluation was performed, and the highest temperature at which blisters were not visually confirmed was taken as the solder heat resistance temperature of the liquid crystal polyester composition. It should be noted that the above evaluation is performed until the temperature of the solder bath reaches 300°C. When no blisters are observed on the surface of the test piece after immersion in a 300°C solder bath, the solder heat resistance temperature of the liquid crystal polyester composition is set to 300°C or higher (≥300°C). The higher the solder heat resistance temperature, the higher the heat resistance of the liquid crystal polyester composition.
[0247] The liquid crystal polyester composition of the embodiment may have a solder heat resistance temperature of 270° C. or higher, or 300° C. or higher, as measured in the above-mentioned [Solder Heat Resistance Test].
[0248] The liquid crystal polyester composition of the embodiment has improved tensile elongation due to the inclusion of the above-mentioned olefin-based copolymer.
[0249] The tensile elongation of the liquid crystal polyester composition of the embodiment can be evaluated by the following [Evaluation of Tensile Elongation] method.
[0250] [Evaluation of tensile elongation]
[0251] Using an injection molding machine (e.g., PNX-40-5A manufactured by Nissei Plastic Industry Co., Ltd.), under the conditions of a barrel temperature of 315 to 320°C, a mold temperature of 130°C, and an injection speed of 75 mm / s, the liquid crystal polyester composition is used as a molding material, and a molded body formed of the liquid crystal polyester composition, i.e., a dumbbell test piece type IV (thickness 2.5 mm) of ASTM D638, is injection molded. For each of the five samples of the obtained dumbbell test pieces, a tensile tester (e.g., TENSILON RTG-1250 manufactured by A&D Co., Ltd.) is used to perform a tensile test at a chuck distance of 50 mm, a crosshead speed of 10 mm / min, and a test temperature of 25°C, and the elongation at this time is measured, and the average value of the tensile elongation (%) at break calculated by the following formula is obtained for the five samples.
[0252] Tensile elongation (%) = (L-Lo) / Lo × 100
[0253] Lo: Length of the distance between the chucks before the test (mm), L: Length of the distance between the chucks at the time of fracture (mm)
[0254] The value of the tensile elongation of the liquid crystal polyester composition of the embodiment measured in the above [Evaluation of Tensile Elongation] may be 4.0% or more, 4.5% or more and 30% or less, or 5.0% or more and 20% or less.
[0255] The liquid crystal polyester composition of the embodiment contains the olefin-based copolymer, so that the melt viscosity does not increase excessively, and the heat resistance and tensile elongation are improved.
[0256] The melt viscosity of the liquid crystal polyester composition of the embodiment can be obtained by the following measuring method.
[0257] 〔Measurement of melt viscosity〕
[0258] A capillary rheometer (LCR7000 manufactured by Dynisco Co., Ltd., Japan) was used. A capillary with an inner diameter of 0.5 mm and a length of 10 mm was installed at the front end of the barrel. The pellets of the liquid crystal polyester composition were melted in a barrel heated to 340° C. and extruded from a nozzle. The viscosity of the extruded liquid crystal polyester composition at a shear rate of 1000 / sec was measured, and the above viscosity was taken as the melt viscosity of the liquid crystal polyester composition.
[0259] The melt viscosity of the liquid crystal polyester composition of the embodiment measured in the above [Measurement of Melt Viscosity] may be 200 Pa·s or less, 150 Pa·s or less, 10 Pa·s or more and 150 Pa·s or more, or 20 Pa·s or more and 100 Pa·s or less.
[0260] The liquid crystal polyester composition of the embodiment can provide a liquid crystal polyester composition having low dielectric constant and dielectric loss tangent by containing the liquid crystal polyester.
[0261] The liquid crystal polyester composition of the embodiment can easily reduce the value of the dielectric loss tangent measured in the following [Dielectric Property Evaluation] because the liquid crystal polyester has a repeating unit Z including a naphthalene structure.
[0262] The dielectric properties of the liquid crystal polyester composition of the embodiment can be determined by the following [Dielectric Property Evaluation].
[0263] 〔Dielectric property evaluation〕
[0264] An injection molding machine (manufactured by FANUC Co., Ltd., ROBOSHOT S-2000i 30B) was used, and the liquid crystal polyester composition was used as a molding material under the conditions of a barrel temperature of 315 to 330°C, a mold temperature of 130°C, and an injection speed of 100 mm / s to obtain a test piece with a width of 50 mm, a length of 50 mm, and a thickness of 0.5 mm formed of the liquid crystal polyester composition. For the obtained test piece, a vector network analyzer (for example, manufactured by Keysight Technologies Co., Ltd., N5290A) and a separated cylindrical resonator (for example, manufactured by EM labs Co., Ltd., CR710) were used to measure the dielectric constant and dielectric loss tangent at 10 GHz in the following measurement environment.
[0265] ·Measurement environment: 23℃, 50%RH
[0266] <Dielectric constant>
[0267] The dielectric constant of the liquid crystal polyester composition of the embodiment at a frequency of 10 GHz measured in the above [Dielectric Property Evaluation] may be 4 or less, 3.8 or less, or 3.6 or less. The dielectric constant of the liquid crystal polyester composition of the embodiment at a frequency of 10 GHz measured in the above [Dielectric Property Evaluation] may be 3 or more, 3.2 or more, or 3.4 or more.
[0268] The upper limit and lower limit of the dielectric constant of the liquid crystal polyester composition can be freely combined. The dielectric constant of the liquid crystal polyester composition can be 3 or more and 4 or less, 3.2 or more and 3.8 or less, or 3.4 or more and 3.6 or less.
[0269] <Dielectric loss tangent>
[0270] The dielectric loss tangent of the liquid crystal polyester composition of the embodiment at a frequency of 10 GHz measured in the above [Dielectric Property Evaluation] may be 0.002 or less, 0.0015 or less, or 0.001 or less. The lower limit of the dielectric loss tangent of the liquid crystal polyester composition of the embodiment at a frequency of 10 GHz measured in the above [Dielectric Property Evaluation] is not particularly limited, but may be 0.0002 or more, 0.0003 or more, or 0.0004 or more.
[0271] The upper limit and lower limit of the dielectric loss tangent of the above-mentioned liquid crystal polyester composition can be freely combined. The dielectric loss tangent of the above-mentioned liquid crystal polyester composition can also be 0.0002 or more and 0.002 or less, 0.0003 or more and 0.0015 or less, or 0.0004 or more and 0.001 or less.
[0272] When the liquid crystal polyester composition of the embodiment contains the liquid crystal polyester (A) and the liquid crystal polyester (B), the viscosity increase due to temperature drop is suppressed and the processing characteristics are improved compared with the composition containing only the liquid crystal polyester (B).
[0273] One embodiment of the liquid crystal polyester composition disclosed herein contains a liquid crystal polyester and an olefin-based copolymer, wherein the olefin-based copolymer contains a repeating unit A derived from an olefin monomer having 2 to 8 carbon atoms and a repeating unit B having a glycidyl group.
[0274] The above-mentioned liquid crystal polyester comprises a liquid crystal polyester (A) and a liquid crystal polyester (B),
[0275] The liquid crystal polyester (A) is a liquid crystal polyester having the repeating unit (A1-3), the repeating unit (A2-3) and the repeating unit (A3-3); the liquid crystal polyester (B) is a liquid crystal polyester having the repeating unit (B1-1-1) and the repeating unit (B1-2-1);
[0276] The mass ratio of the liquid crystal polyester (A) to the liquid crystal polyester (B) is 90 / 10 to 60 / 40, preferably 60 / 40.
[0277] In the olefin-based copolymer, the content of the repeating unit A is 93% by mass or more and 98% by mass or less, and the content of the repeating unit B is 2% by mass or more and 7% by mass or less (preferably, the content of the repeating unit A is 94.5% by mass or more and 98% by mass or less, and the content of the repeating unit B is 2% by mass or more and 5.5% by mass or less, and more preferably, the content of the repeating unit A is 97% by mass or more and 98% by mass or less, and the content of the repeating unit B is 2% by mass or more and 3% by mass or less), relative to the total mass of the olefin-based copolymer.
[0278] Relative to the total mass of the above-mentioned liquid crystal polyester composition, the content of the above-mentioned liquid crystal polyester is greater than 90 mass% and less than 97 mass%, and the content of the above-mentioned olefin-based copolymer is greater than 3 mass% and less than 10 mass% (preferably: the content of the above-mentioned liquid crystal polyester is greater than 90 mass% and less than 95 mass%, and the content of the above-mentioned olefin-based copolymer is greater than 5 mass% and less than 10 mass%, and more preferably: the content of the above-mentioned liquid crystal polyester is greater than 88 mass% and less than 92 mass%, and the content of the above-mentioned olefin-based copolymer is greater than 8 mass% and less than 12 mass%).
[0279] 《Method for producing liquid crystal polyester composition》
[0280] The method for producing a liquid crystal polyester composition according to an embodiment includes mixing a liquid crystal polyester with an olefin-based copolymer, wherein the olefin-based copolymer includes a repeating unit A and a repeating unit B.
[0281] According to the method for producing a liquid crystal polyester composition according to the embodiment, the liquid crystal polyester composition according to the embodiment can be produced.
[0282] The liquid crystal polyester composition of the embodiment can be obtained by mixing the above-mentioned liquid crystal polyester, olefin-based copolymer, and optional components used as needed together or in an appropriate order.
[0283] The above-mentioned mixing is preferably performed by melt kneading, and a mixture containing the liquid crystal polyester, the olefin-based copolymer and, if necessary, the optional components may be melt kneaded.
[0284] When the liquid crystal polyester comprises the above-mentioned liquid crystal polyester (A) and the liquid crystal polyester (B), the above-mentioned mixing may also include mixing the above-mentioned liquid crystal polyester (A) and the above-mentioned liquid crystal polyester (B). For example, the liquid crystal polyester (A) and the liquid crystal polyester (B) obtained by pre-polymerization separately can be listed.
[0285] The liquid crystal polyester composition of the present embodiment can be provided as pellets by melt-kneading the liquid crystal polyester, the olefin-based copolymer, and the optional components used as required using an extruder, and then pelletizing the mixture.
[0286] Regarding the liquid crystal polyester, the olefin-based copolymer, and the optional components in the method for producing the liquid crystal polyester composition of the embodiment, and the amounts thereof, the contents described in the above-mentioned "Liquid Crystalline Polyester Composition" can be exemplified.
[0287] From the viewpoint of easily exerting the characteristics of the liquid crystal polyester, the ratio of the amount of the above-mentioned liquid crystal polyester to the above-mentioned olefin-based copolymer in the method for manufacturing the liquid crystal polyester composition of the embodiment can be, by mass ratio, liquid crystal polyester / olefin-based copolymer = 99.9 / 0.1 to 50 / 50, can be 99.5 / 0.5 to 70 / 30, can be 99 / 1 to 80 / 20, or can be 97 / 3 to 90 / 10.
[0288] Regarding the ratio of the amount of the above-mentioned liquid crystal polyester and the above-mentioned olefin-based copolymer in the method for producing the liquid crystal polyester composition of the embodiment, relative to the total mass of 100 mass% of the liquid crystal polyester composition of the embodiment, the liquid crystal polyester may be 50 mass% to 99.9 mass% and the olefin-based copolymer may be 0.1 mass% to 50 mass%; the liquid crystal polyester may be 80 mass% to 99.9 mass% and the olefin-based copolymer may be 0.1 mass% to 20 mass%; the liquid crystal polyester may be 90 mass% to 99 mass% and the olefin-based copolymer may be 1 mass% to 10 mass%; the liquid crystal polyester may be 95 mass% to 97 mass% and the olefin-based copolymer may be 3 mass% to 5 mass%.
[0289] The liquid crystal polyester composition of the embodiment obtained in this way, in particular, pellets of the liquid crystal polyester composition of the embodiment can be suitably used as a molding material composition used for production of a molded product described later.
[0290] Forming
[0291] The molded article of the embodiment includes the liquid crystal polyester composition of the embodiment described above. The molded article of the embodiment is a connector, a socket, a relay component, a coil frame, an optical pickup, an oscillator, a semiconductor package, an IC tray, a wafer carrier, a household electrical appliance component, a lighting fixture component, an audio product component, a ferrule for an optical cable, a telephone component, a fax component, a modem component, a separation claw, a heater bracket, an impeller, a fan gear, a gear, a bearing, a motor component, a motor housing, an engine component, an engine room component, an electrical component, an automobile interior decoration component, a microwave cooking pot, a heat-resistant tableware, a floor material, a wall material, a beam, a column, a roof material, an aircraft component, a spacecraft component, a space equipment component, a nuclear reactor, a marine facility component, a washing fixture, an optical equipment component, a valve, a pipe, a nozzle, a filter, a membrane, a medical equipment component, a medical material, a sensor component, a sanitary component, a sporting good, or a leisure product.
[0292] The molded article of the present embodiment may be composed only of the liquid crystal polyester composition of the embodiment, and examples thereof include connectors, sockets, relay parts, coil bobbins, optical pickups, oscillators, semiconductor packages, IC trays, wafer carriers, household electrical appliance parts, lighting fixture parts, audio product parts, ferrules for optical cables, telephone parts, fax parts, modem parts, separation claws, heater holders, impellers, fan gears, gears, bearings, motor parts, motor housings, engine parts, engine room parts, electrical parts, automobile interior parts, microwave cooking pots, heat-resistant tableware, floor materials, wall materials, beams, columns, roof materials, aircraft parts, spacecraft parts, aerospace equipment parts, nuclear reactors, marine facility components, washing jigs, optical equipment parts, valves, pipes, nozzles, filters, membranes, medical equipment parts, medical materials, sensor parts, sanitary parts, sports goods, or leisure goods.
[0293] The molded article of the embodiment can be obtained, for example, by molding the liquid crystal polyester composition of the embodiment described above into a desired shape and subjecting the molded article to processing as necessary.
[0294] As a molding method, melt molding is preferred. Examples of the melt molding method include injection molding, extrusion molding, compression molding, blow molding, vacuum molding, foam molding, and press molding.
[0295] Since the molded article of the embodiment includes the liquid crystal polyester composition of the embodiment, it is an excellent molded article with improved heat resistance and tensile elongation as shown as the results of measurement in the above-mentioned respective evaluations.
[0296] Example
[0297] Next, the present disclosure will be described in further detail with reference to examples, but the present disclosure is not limited to the following examples.
[0298] 《Measurement / Evaluation》
[0299] The following measurements and evaluations were performed using each liquid crystal polyester produced below, or a liquid crystal polyester composition obtained in each Example or Comparative Example, or a test piece thereof as a sample to be measured.
[0300] 〔Measurement of flow start temperature〕
[0301] Using a flow tester (manufactured by Shimadzu Corporation, CFT-500 model), about 2 g of pellets of the liquid crystal polyester or liquid crystal polyester composition were filled into a cylinder equipped with a die having a nozzle with an inner diameter of 1 mm and a length of 10 mm, and the mixture was stirred at 9.8 MPa (100 kg / cm 2 ) under a load of 4°C / min, while the liquid crystal polyester composition is melted, extruded from a nozzle, and the temperature (FT) showing a viscosity of 4800 Pa·s (48000P) is measured, and the above temperature is taken as the flow start temperature. "About 2g" can be estimated as 2g±0.1g.
[0302] 〔Measurement of melt viscosity〕
[0303] A capillary rheometer (LCR7000 manufactured by Dynisco Co., Ltd., Japan) was used. A capillary with an inner diameter of 0.5 mm and a length of 10 mm was installed at the front end of the barrel. The pellets of the liquid crystal polyester composition were melted in a barrel heated to 340° C. and extruded from a nozzle. The viscosity of the extruded liquid crystal polyester composition at a shear rate of 1000 / sec was measured, and the above viscosity was taken as the melt viscosity of the liquid crystal polyester composition.
[0304] 〔Solder heat resistance test〕
[0305] Using an injection molding machine (PNX-40-5A manufactured by Nissei Plastic Industry Co., Ltd.), under the conditions shown in Table 1, pellets of the liquid crystal polyester composition were used as molding materials to produce a molded body formed of the liquid crystal polyester composition, namely a dumbbell test piece (thickness 1.2 mm) of JIS K7113 (1 / 2). The obtained dumbbell test piece was immersed in a solder bath ("L20" Sn / Bi=42 / 58 manufactured by Senju Metal Industry Co., Ltd.) heated to a predetermined temperature for 60 seconds, and after being taken out, it was visually confirmed whether blisters were seen on the surface of the above test piece. The temperature of the solder bath was increased by 5°C each time and the same evaluation was performed, and the highest temperature at which blisters were not visually confirmed was taken as the solder heat resistance temperature of the liquid crystal polyester composition. It should be noted that the above evaluation was performed until the temperature of the solder bath reached 300°C. When no blisters were seen on the surface of the test piece after being immersed in a solder bath at 300°C, the solder heat resistance temperature of the liquid crystal polyester composition was set to 300°C or more (≥300°C).
[0306] [Table 1]
[0307] Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Barrel temperature ℃ 315 315 320 315 315 315 315 315 Mold temperature ℃ 130 130 130 130 130 130 130 130 Injection speed mm / s 75 75 75 75 75 75 75 75
[0308] [Evaluation of tensile elongation]
[0309] An injection molding machine (manufactured by Nissei Plastic Industry Co., Ltd., PNX-40-5A) was used to injection mold ASTM D638 dumbbell test pieces type IV (thickness 2.5 mm) formed of the liquid crystal polyester composition under the conditions shown in Table 1 using pellets of the liquid crystal polyester composition as molding materials. Five samples of the obtained dumbbell test pieces were subjected to a tensile test using a tensile testing machine (manufactured by A&D, TENSILON RTG-1250) at a chuck distance of 50 mm, a crosshead speed of 10 mm / min, and a test temperature of 25° C. The elongation at this time was measured, and the average value of the tensile elongation (%) at break of the five samples was calculated.
[0310] The tensile elongation was calculated by the following formula.
[0311] Tensile elongation (%) = (L-Lo) / Lo × 100
[0312] Lo: Length of the distance between the chucks before the test (mm), L: Length of the distance between the chucks at the time of fracture (mm)
[0313] 〔Dielectric property evaluation〕
[0314] An injection molding machine (manufactured by FANUC Corporation, ROBOSHOT S-2000i 30B) was used to obtain a test piece having a width of 50 mm, a length of 50 mm, and a thickness of 0.5 mm formed of the liquid crystal polyester composition using pellets of the liquid crystal polyester composition as molding materials under the conditions shown in Table 2. The obtained test piece was measured for the dielectric constant and dielectric loss tangent at 10 GHz using a vector network analyzer (manufactured by Keysight Technologies Corporation, N5290A) and a separated cylindrical resonator (manufactured by EM labs Corporation, CR710).
[0315] ·Measurement environment: 23℃, 50%RH
[0316] [Table 2]
[0317] Comparative Example 1 Comparative Example 2 Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Barrel temperature ℃ 315 315 330 315 315 315 315 315 Mold temperature ℃ 130 130 130 130 130 130 130 130 Injection speed mm / s 100 100 100 100 100 100 100 100
[0318] 《Manufacturing example》
[0319] [Manufacture of liquid crystal polyester (LCP-1)]
[0320] In a reactor equipped with a stirrer, a torque meter, a nitrogen inlet pipe, a thermometer, and a reflux cooler, 1034.99 g (5.5 mol) of 2-hydroxy-6-naphthoic acid, 378.33 g (1.75 mol) of 2,6-naphthalenedicarboxylic acid, 83.07 g (0.5 mol) of terephthalic acid, 272.52 g (2.475 mol, 0.225 mol excess relative to the total molar amount of 2,6-naphthalenedicarboxylic acid and terephthalic acid), 1226.87 g (12 mol) of acetic anhydride, and 0.17 g of 1-methylimidazole as a catalyst were added. After replacing the gas in the reactor with nitrogen, the temperature was raised from room temperature to 145° C. over 15 minutes while stirring under a nitrogen flow, and refluxed at 145° C. for 1 hour.
[0321] Next, while removing by-produced acetic acid and unreacted acetic anhydride by distillation, the temperature was raised from 145°C to 310°C over 3 hours and 30 minutes, and after being kept at 310°C for 3 hours, the contents were taken out and cooled to room temperature. The obtained solid was pulverized with a pulverizer to obtain a powdery liquid crystal polyester (a1).
[0322] Liquid crystal polyester (a1) was subjected to solid phase polymerization under nitrogen atmosphere by heating from room temperature to 240°C for 25 minutes, then from 240°C to 250°C for 10 minutes, then from 250°C to 288°C for 6 hours and 20 minutes, and then kept at 288°C for 5 hours to obtain a powdered liquid crystal polyester (LCP-1). The flow start temperature of the liquid crystal polyester (LCP-1) was 313°C.
[0323] [Manufacture of liquid crystal polyester (LCP-2)]
[0324] 1511.1 g (8.03 mol) of 2-hydroxy-6-naphthoic acid, 410.2 g (2.97 mol) of p-hydroxybenzoic acid, 1291.4 g (12.65 mol) of acetic anhydride and 0.058 g of 1-methylimidazole as a catalyst were added to a reactor equipped with a stirring device, a torque meter, a nitrogen inlet pipe, a thermometer and a reflux cooler. After replacing the gas in the reactor with nitrogen, the temperature was raised from room temperature to 145° C. over 15 minutes while stirring under a nitrogen flow, and refluxed at 145° C. for 1 hour.
[0325] Next, while removing the by-product acetic acid and unreacted acetic anhydride by distillation, the temperature was raised from 145°C to 275°C in 2 hours and 40 minutes. After being kept at 275°C for 3 hours, the contents were taken out and cooled to room temperature. The obtained solid was crushed with a grinder to obtain a powdered liquid crystal polyester (LCP-2). The flow start temperature of the liquid crystal polyester (LCP-2) was 292°C.
[0326] [Manufacture of liquid crystal polyester (LCP-3)]
[0327] In a reactor equipped with a stirrer, a torque meter, a nitrogen inlet pipe, a thermometer, and a reflux cooler, 1035.0 g (5.5 mol) of 2-hydroxy-6-naphthoic acid, 378.3 g (1.75 mol) of 2,6-naphthalenedicarboxylic acid, 83.1 g (0.5 mol) of terephthalic acid, 255.2 g (2.31 mol) of hydroquinone, 1226.87 g (12 mol) of acetic anhydride, and 0.17 g of 1-methylimidazole as a catalyst were added. After replacing the gas in the reactor with nitrogen, the temperature was raised from room temperature to 140° C. over 30 minutes while stirring under a nitrogen flow, and refluxed at 140° C. for 1 hour.
[0328] Next, while removing the by-product acetic acid and unreacted acetic anhydride by distillation, the temperature was raised to 310°C in 4 hours and 35 minutes. When the torque rise was confirmed, the reaction was considered to be complete, and the contents were taken out, cooled to room temperature, and crushed with a pulverizer. The obtained solid was heated from room temperature to 250°C in 1 hour under a nitrogen atmosphere, from 250°C to 280°C in 5 hours, and kept at 280°C for 6 hours to polymerize it in the solid phase to obtain a powdered liquid crystal polyester (LCP-3). The flow start temperature of the liquid crystal polyester (LCP-3) was 301°C.
[0329] [Manufacturing of olefin copolymers]
[0330] As a raw material for preparing a liquid crystal polyester composition, the following olefin-based copolymer was prepared.
[0331] (EGMA-1) Sumitomo Chemical Co., Ltd., "BF-2C" random copolymer of 93.6 mass % ethylene and 6.4 mass % glycidyl methacrylate, MFR = 3 g / 10 min (polymerization pressure: 1346 kg / cm 2 , polymerization temperature: 194℃)
[0332] (EGMA-2) Random copolymer of 97.7 mass % ethylene and 2.3 mass % glycidyl methacrylate, MFR = 43 g / 10 min (polymerization pressure: 1356 kg / cm 2 , polymerization temperature: 195℃)
[0333] (EGMA-3) Random copolymer of 97.7 mass % ethylene and 2.3 mass % glycidyl methacrylate, MFR = 190 g / 10 min (polymerization pressure: 1356 kg / cm 2 , polymerization temperature: 195℃)
[0334] [Example 1]
[0335] The powdered liquid crystal polyester (LCP-1), liquid crystal polyester (LCP-2) and olefin copolymer (EGMA-1) obtained above were mixed in a mass ratio of LCP-1 / LCP-2 / EGMA-1=54 / 36 / 10 to obtain a liquid crystal polyester composition. Next, a twin-screw extruder (manufactured by Ikegai Iron Works Co., Ltd., PCM-30) was used to granulate the liquid crystal polyester composition at a barrel temperature of 330° C. to obtain pellets of the liquid crystal polyester composition of Example 1.
[0336] [Example 2]
[0337] The liquid crystal polyester (LCP-1), the liquid crystal polyester (LCP-2) and the olefin copolymer (EGMA-2) were mixed in a mass ratio of LCP-1 / LCP-2 / EGMA-2=58.2 / 38.8 / 3. Except for this, the same operation as in Example 1 was carried out to obtain pellets of the liquid crystal polyester composition of Example 2.
[0338] [Example 3]
[0339] The liquid crystal polyester (LCP-1), the liquid crystal polyester (LCP-2) and the olefin copolymer (EGMA-2) were mixed in a mass ratio of LCP-1 / LCP-2 / EGMA-2=57 / 38 / 5. Except for this, the same operation as in Example 1 was carried out to obtain pellets of the liquid crystal polyester composition of Example 3.
[0340] [Example 4]
[0341] The liquid crystal polyester (LCP-1), the liquid crystal polyester (LCP-2) and the olefin copolymer (EGMA-2) were mixed in a mass ratio of LCP-1 / LCP-2 / EGMA-2=54 / 36 / 10. The same operation as in Example 1 was carried out to obtain pellets of the liquid crystal polyester composition of Example 4.
[0342] [Example 5]
[0343] The liquid crystal polyester (LCP-1), the liquid crystal polyester (LCP-2) and the olefin copolymer (EGMA-3) were mixed in a mass ratio of LCP-1 / LCP-2 / EGMA-3=58.2 / 38.8. / 3. Except for this, the same operation as in Example 1 was carried out to obtain pellets of the liquid crystal polyester composition of Example 5.
[0344] [Example 6]
[0345] Pellets of a liquid crystal polyester composition of Example 6 were obtained in the same manner as in Example 1 except that the liquid crystal polyester (LCP-3) and the olefin copolymer (EGMA-2) were mixed at a mass ratio of LCP-3 / EGMA-2=97 / 3.
[0346] [Comparative Example 1]
[0347] Pellets of a liquid crystal polyester composition of Comparative Example 1 were obtained in the same manner as in Example 1 except that the liquid crystal polyester (LCP-1) and the liquid crystal polyester (LCP-2) were mixed at a mass ratio of LCP-1 / LCP-2=60 / 40.
[0348] [Comparative Example 2]
[0349] Pellets of a liquid crystal polyester composition of Comparative Example 2 were obtained in the same manner as in Example 1 except that the liquid crystal polyester (LCP-3) was used.
[0350] Table 3 shows the amounts of the above-mentioned ingredients, measurements, and evaluation results.
[0351]
[0352] In Examples 1 to 6 containing the olefin-based copolymer, the solder heat resistance temperature was increased and the tensile elongation was also improved compared to Comparative Examples 1 and 2 not containing the olefin-based copolymer.
[0353] In addition, referring to Examples 2 to 4, it was confirmed that the tensile elongation increased as the content ratio of the olefin-based copolymer increased.
[0354] Each composition of Examples 1 to 6 contained a liquid crystal polyester having a repeating unit including a naphthalene structure, had a low dielectric constant and a low dielectric loss tangent, and exhibited good dielectric properties.
[0355] It should be noted that, although the dielectric loss tangent tends to slightly increase as the content ratio of the olefin-based copolymer increases, referring to Examples 1 and 4, Example 4, in which the content ratio of the repeating unit B of the olefin-based copolymer is less than 6% by mass, suppresses the increase in the dielectric loss tangent more than Example 1.
[0356] In addition, Examples 2 to 6 in which the content of the repeating unit B in the olefin-based copolymer was less than 6% by mass, the melt viscosity was further suppressed and the tensile elongation was improved.
[0357] The above results show that the liquid crystal polyester compositions of Examples 1 to 5 to which the present disclosure is applied have excellent solder heat resistance, tensile elongation, and dielectric properties.
[0358] Each configuration and combination thereof in each embodiment is an example, and addition, omission, substitution, and other changes of configurations may be made without departing from the gist of the present disclosure. The present disclosure is not limited to each embodiment, but is limited only to the scope of the claims.
[0359] Industrial Applicability
[0360] According to the present disclosure, a liquid crystal polyester composition having excellent heat resistance and tensile elongation can be provided. In addition, according to the present disclosure, a method for producing a liquid crystal polyester composition having excellent heat resistance and tensile elongation can be provided. In addition, according to the present disclosure, a molded body comprising the liquid crystal polyester composition can be provided.
Claims
1. A liquid crystal polyester composition comprising: Liquid crystal polyester, and Olefin copolymers, The olefin-based copolymer includes a repeating unit A derived from an olefin monomer having 2 to 8 carbon atoms and a repeating unit B having a glycidyl group.
2. The liquid crystal polyester composition according to claim 1, wherein The liquid crystal polyester has a repeating unit including a naphthalene structure, and the content of the repeating unit including a naphthalene structure is 40% or more relative to 100% of the total number of all repeating units in the liquid crystal polyester.
3. The liquid crystal polyester composition according to claim 1 or 2, wherein The liquid crystal polyester has a repeating unit derived from a hydroxycarboxylic acid, and the content of the repeating unit derived from the hydroxycarboxylic acid is more than 50% based on 100% of the total number of all repeating units in the liquid crystal polyester.
4. The liquid crystal polyester composition according to claim 1 or 2, wherein The content of the repeating unit B is less than 6% by mass based on 100% by mass of the total mass of the olefin-based copolymer.
5. The liquid crystal polyester composition according to claim 1 or 2, wherein The content of the repeating unit A is more than 94% by mass based on 100% by mass of the total mass of the olefin-based copolymer.
6. The liquid crystal polyester composition according to claim 1 or 2, wherein: The flow start temperature was over 271°C.
7. The liquid crystal polyester composition according to claim 1 or 2, wherein: The content of the liquid crystal polyester is 80% by mass or more relative to 100% by mass of the total mass of the liquid crystal polyester composition.
8. The method for producing a liquid crystal polyester composition according to claim 1 or 2, comprising mixing a liquid crystal polyester with an olefin copolymer, The olefin-based copolymer includes a repeating unit A derived from an olefin monomer having 2 to 8 carbon atoms and a repeating unit B having a glycidyl group.
9. A molded product comprising the liquid crystal polyester composition according to claim 1 or 2, in, The molded body is a connector, a socket, a relay component, a coil skeleton, an optical pickup, an oscillator, a semiconductor package, an IC tray, a wafer carrier, a household electrical product component, a lighting device component, an audio product component, a ferrule for an optical cable, a telephone component, a fax component, a modem component, a separation claw, a heater bracket, an impeller, a fan gear, a gear, a bearing, a motor component, a motor housing, an engine component, an engine room component, an electrical component, an automobile interior decoration component, a microwave cooking pot, a heat-resistant tableware, a floor material, a wall material, a beam, a column, a roof material, an aircraft component, a spacecraft component, a space equipment component, a nuclear reactor, a marine facility component, a washing fixture, an optical equipment component, a valve, a pipe, a nozzle, a filter, a membrane, a medical equipment component, a medical material, a sensor component, a sanitary spare part, a sports product or a leisure product.
Citation Information
Patent Citations
Analytical method for composition of total aromatic liquid crystal polyester resin
JP2000019168A
Travel control device, travel control method and computer program for travel control
JP2022149236A
Communication device and communication method
JP2023003766A
Resin composition, and resin molded article comprising said resin composition
WO2020138277A1